2001
DOI: 10.1111/j.1945-5100.2001.tb01853.x
|View full text |Cite
|
Sign up to set email alerts
|

Space weathering on Eros: Constraints from albedo and spectral measurements of Psyche crater

Abstract: Abstract-We present combined multi-spectral imager (MSI) (0.95 pm) and near-infrared spectrometer (NIS) (0.8-2.4pm) observations of Psyche crater on S-type asteroid 433 Eros obtained by the NearEarth Asteroid Rendezvous (NEAR)-Shoemaker spacecraft. At 5.3 km in diameter, Psyche is one of the largest craters on Eros which exhibit distinctive brightness patterns consistent with downslope motion of dark regolith material overlying a substrate of brighter material. At spatial scales of620 m/ spectrum, Psyche crate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 44 publications
4
76
0
Order By: Relevance
“…The so-called ordinary chondrite paradox, that is lack of asteroids similar to the ordinary chondrites, which represent 80% of meteorite falls, has been solved. These meteorites are now clearly related to S-type asteroids, as proved by direct measurements of the NEAR and HAYABUSA missions on the near Earth asteroids Eros and Itokawa (Clark et al 2001;Noguchi et al 2011) and laboratory experiments on irradiation of silicates/ordinary chondrites (Moroz et al 1996;Sasaki et al 2002;Brunetto & Strazzulla 2005;Noble et al 2007). Spectral differences between S-type asteroids and ordinary chondrites are caused by space weathering effects, which produce a darkening in the albedo, a reddening of the spectra, and diminish the silicates absorption bands on the asteroids surfaces, exposed to cosmic radiation and solar wind.…”
Section: Scenario C): the Family Parent Body Was Homogeneous And The mentioning
confidence: 82%
“…The so-called ordinary chondrite paradox, that is lack of asteroids similar to the ordinary chondrites, which represent 80% of meteorite falls, has been solved. These meteorites are now clearly related to S-type asteroids, as proved by direct measurements of the NEAR and HAYABUSA missions on the near Earth asteroids Eros and Itokawa (Clark et al 2001;Noguchi et al 2011) and laboratory experiments on irradiation of silicates/ordinary chondrites (Moroz et al 1996;Sasaki et al 2002;Brunetto & Strazzulla 2005;Noble et al 2007). Spectral differences between S-type asteroids and ordinary chondrites are caused by space weathering effects, which produce a darkening in the albedo, a reddening of the spectra, and diminish the silicates absorption bands on the asteroids surfaces, exposed to cosmic radiation and solar wind.…”
Section: Scenario C): the Family Parent Body Was Homogeneous And The mentioning
confidence: 82%
“…Sarnus has a more intriguing behavior, since it shares characteristics of Gallicum and Danuvius Labes, it is spectrally closer to the latter, but it has similar normal albedo to Gallicum Labes. If compared to Psyche Crater in (433) Eros (Clark et al, 2001), the correlation is opposite, the variegation is larger (32-40%), but spectrally, the dark material at the bottom of the crater and the bright material on the walls, show no more than 4-8% of difference. Thus, we have confirmed that the variegation and spectral differences between crater walls are significant, as hinted by the small phase angle images of (21) Lutetia.…”
Section: Discussionmentioning
confidence: 98%
“…In dashed black lines are the +σ and -σ from the mean. We chose this type of ratio plot to be consistent with other studies showing the spectral effects of surface alteration on higher albedo asteroids (Clark et al 2001). Asteroid data were smoothed before ratioing to avoid high frequency variations and focus only on low frequency behavior.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…The effects of space weathering on S-type asteroids have been widely analyzed (Moroz et al 1996;Clark et al 2001;Brunetto et al 2005;Ishiguro et al 2007). Because S-types have high albedos and strong absorption band features, space weathering effects are easier to detect.…”
Section: Introductionmentioning
confidence: 99%